Differential Expression of the TLR4 Gene in Pan-Cancer and Its Related Mechanism - Hu, Jialing; Xu, Jiasheng; Feng, Xiaojin; Li, Yiran; Hua, Fuzhou; Xu, Guohai (Frontiers in Cell and Developmental Biology, 2021)
Studies have revealed the relationship between TLR4 polymorphism and cancer susceptibility. However, the relationship between TLR4 and prognosis and immune cell infiltration in pan-cancer patient is still unclear. Through GTEx and TCGA databases, the distinction expression of TLR4 gene in 24 tumors and normal tissues was analyzed. Univariate Cox proportional hazard regression analysis was used to sort out the cancer types whose TLR4 gene expression is related to prognosis. The relationship between TLR4 and tumor cell immune invasion was studied. Spearman's rank correlation coefficient was used to analyze the relationship among TLR4 with immune neoantigen, TMB, MSI, DNA repair genes and DNA methylation. Using GSEA to analyze which tumor-related pathways the TLR4 gene is highly expressed; the expression of TLR4 gene was verified by HPA database. Studies have found that low expression of TLR4 was concerned with inferior prognosis in KIRC, SKCM and UCEC, while high expression was connected with impoverished prognosis in HNSC, PRAD, STAD and TGCT. The expression of TLR4 was negatively correlated to the expression of B cells in STAD. The expression of TLR4 was correlated positively with the infiltration of B cells, CD4 and CD8 T cells, neutrophils, macrophages and dendritic cells in STAD, KIRC, UCEC, TGCT and SKCM. The expression of TLR4 gene in KIRC, SKCM, STAD, TGCT and UCEC was highly correlated with ICOS, CTLA4, CD28 et al immune checkpoints. Spearman's rank correlation coefficient showed that the expression of TLR4 gene was significantly correlated with TMB in STAD and UCEC, and was prominently correlated with MSI in TGCT, STAD, SKCM. The expression of TLR4 gene is highly correlated with MLH1, MSH2, MSH6 in KIRC, SKCM and STAD. The expression of TLR4 gene was remarkably correlated with methyltransferase DNMT2 and DNMT3B in SKCM and STAD. Enrichment analysis showed that TLR4 was highly expressed in the chemokine signaling pathway, cell adhesion molecule and cytokine receptor interaction pathway. In summary, the expression of TLR4 is linked to the prognosis of KIRC, SKCM, STAD, TGCT, UCEC patients, and the level of immune infiltration of CD4, CD8T cells, macrophages, neutrophils, and dendritic cells.